Concise Diastereoselective Total Synthesis of (±)-Parvistemonine A - Matsuo, Rintaro; Miyashita, Ayumu; Kuwabara, Motoi; Adachi, Shinya; Matsuzawa, Akinobu; Sugita, Kazuyuki (Synlett, 2020)
We have developed a concise diastereoselective total synthesis of (±)-parvistemonine A. By using a Mukaiyama–Michael addition, an aza-Wittig reaction, a Paal–Knorr pyrrole synthesis, an acid-mediated annulation, and a Mitsunobu reaction as key steps, we achieved a total synthesis in which the longest linear sequence was ten steps and the overall yield was 19.6%. Additionally, the relative stereochemistry of parvistemonine A was confirmed by X-ray crystallographic analysis for the first time.
Keywords: parvistemonine A; natural product; total synthesis; aza-Wittig reaction; Mitsunobu reaction